The use of an Intra-medullary fusion system in hammer toe surgery; mid-term follow-up - Turan Cihan Dulgeroglu; Karaaslan, Fatih (Journal of the Pakistan Medical Association, 2023)
Objective: To assess the efficacy of a new hammer-toe locking fusion system. Method: The retrospective study was conducted at Kutahya Evliya Çelebi Education and Research Hospital, and comprised data from March 2014 to January 2017 of patients of either gender with hammer toe deformity. The American Orthopaedic Foot and Ankle Society and visual analogue scale scoring systems were used. Radiological evaluation was also used to determine the lateral interphalangeal angle measurements. All patients were subjected to hammer toe surgery using new two-block interlocking fusion system, and were followed up for about 2 years. SPSS 25.0 for windows was used for analysis. Results: According to gender, 13(65%) of patients were female and 7(35%) of patients were male. The overall mean age was 51.5±16.31 years (range: 20-72 years). Of all the surgeries, 9(45%) were performed on the right foot, and 11(55%) on the left foot. The follow-ups ranged 21-32 months. Compared to baselines values, American Orthopaedic Foot and Ankle Society scale and visual analogue scale scores significantly improved post intervention (p<0.05). Conclusion: Significantly favourable outcomes were noted, indicating the efficacy of the fusion process. Key Words: Toes, Hammer, Interphalangeal, Lesser toe, Arthrodesis.